Deskripsi Fatigue Pekerja Divisi Welltech XYZ - Hari Prayogo; Fierdania Yusvita; Rini Handayani; Veza Azteria; Cut Alia Keumala Muda (Pusat Riset dan Inovasi Nasional, 2023)
Based on the researchers' initial observations of 17 workers in the Welltech Division of PT XYZ, it was found that 95% of the workers had health problems that could be related to work, such as cholesterol above normal limits, blood sugar above normal limits, spots on the lungs, and so on. Analyse the picture of work-related fatigue in the Welltech Division workers of PT XYZ. This study has a sample of 55 people with accidental sampling technique, type of quantitative method using analytical survey and descriptive approach. Data collection techniques used in this quantitative research are questionnaires and answer choices that have been prepared in advance. The questionnaire was distributed using Google Form. Based on the univariate results, the picture of job fatigue in workers the highest proportion of respondents experienced moderate fatigue, namely 32 people (58.2%), the picture of weakening activity in workers the highest proportion of respondents experienced moderate fatigue, namely 27 people (49.1%), the picture of weakening motivation in workers the highest proportion of respondents experienced moderate fatigue, namely 37 people (67.3%), the picture of physical weakening in workers the highest proportion of respondents experienced moderate fatigue, namely 32 people (58.2%),. It is hoped that companies will improve health programmes or work programme arrangements and then implement them for workers to prevent fatigue.